A Comparison of Methods for the Extraction of Plasmids Capable of Conferring Antibiotic Resistance in a Human Pathogen From Complex Broiler Cecal Samples - Delaney, Sarah; Murphy, Richard; Walsh, Fiona (Frontiers in Microbiology, 2018)
The direct extraction of plasmid DNA containing antibiotic resistance genes from complex samples is imperative when studying plasmid-mediated antibiotic resistance from a One Health perspective, in order to obtain a wide representation of all the resistance plasmids present in these microbial communities. There are also relatively few bacterial species from natural environments which can be cultured in vitro. Extracting plasmids from the cultivable fraction of these complex microbiomes may only represent a fraction of the total antibiotic resistance plasmids present. We compared different methods of plasmid extraction from broiler cecal samples, whose resistance could be expressed in a human pathogen - Escherichia coli. We found that kits designed for DNA extraction from complex samples such as soil or faeces did not extract intact plasmid DNA. Commercial kits specific for plasmid extraction were also generally unsuccessful, most likely due to the complexity of our sample and intended use of the kits with bacterial culture. An alkaline lysis method specific for plasmid extraction was ineffective, even with further optimisation. Transposon-aided capture of plasmids (TRACA) allowed for the acquirement of a small range of resistance plasmids. Multiple displacement amplification provided the broadest range of resistance plasmids by amplifying all extracted circular plasmid DNA, but the results were not reproducible across all samples. Exogenous plasmid isolation enabled the extraction of resistance plasmids from the microbial fraction by relying on the mobility of the plasmids in the sample. This was the most consistent method from which we obtained a range of resistance plasmids from our samples. We therefore recommend the use of the exogenous plasmid isolation method in order to reliably obtain the greatest representation of the total antibiotic resistance plasmidome in complex samples. While this method has limitations, it is one which will vastly increase our current knowledge of antibiotic resistance plasmids present in complex environments and which are capable of transferring to a human and animal pathogen and environmental contaminant.